An AI powered nutrition information mobile application - Kwa, Daniel Shen Jun (Nanyang Technological University, 2023)
Food labels with nutrition information contain vital sources of information which should be referred to, but it is not being utilized by consumers when buying them. The importance of having nutrition information is to display key nutrients that can impact consumer’s health and help them reconsider their food choices. Given a key role Artificial Intelligence (AI) will play in impacting people’s lives and the increasing number of smartphone users indicated by statistics, the aim of the project is to develop an Android application that can generate nutritional information by taking pictures or uploading images. The application can also save and share the generated image. Android Studio with Flutter Software Develop Kit (SDK) will be used to develop the mobile application and Python will be used to train AI models using both TensorFlow Lite and Google Colab.